Analysis of the impact of the selected methodology for thermal bridges assessment on the energy balance of a building - Alsabry, Abdrahman; Łaskawiec, Kamil; Szymański, Krzysztof; Rojek, Łukasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
The article presents an analysis of the impact of the selected methodology for thermal bridges assessment on the energy balance on the example of a typical single-family building project. Analytical calculations clearly show that the adopted methodology for determining the value of the coefficient of linear heat transfer of thermal bridge, significantly affects the energy performance of the building. The values of linear heat transfer coefficient presented in thermal bridge catalogs for specific partitions, most often system solutions of various companies, give more precise values than those adopted on the basis of a simplified methodology in accordance with the PN-EN ISO 14683: 2008 standard. Using computer calculations in accordance with the PN-EN ISO 10211: 2008 standard, the values of the linear heat transfer coefficient are a reflection of the actual construction details. It can therefore be clearly stated that these calculations are the most accurate. However, compared to catalogs, this method requires much more work. The change in the method of taking into account the value of the thermal bridge may change the value of the non-renewable primary energy index by up to 20 [kWh/m2a]. Particular attention to precise analyzes of heat losses by thermal bridges should be taken into account when designing passive and zero-energy buildings in which the influence of thermal bridges may constitute more than 20% of the total heat demand.